#TITLE_ALTERNATIVE# - SALMAYARISTA (NIM : 15112083), AJENG
Theory of civilization during Pleistocene epoch in Sundaland is hypothesized due to the coincident three times between human dispersal, sea level rise event, and paleo-environment conditions. Since remnants are most probably submerged in Java Sea, there is a very few reliable records to contextualize such a theory. This study discusses paleo-river model, as inland water resource plays a critical role to sustain lives for humans. Here, paleo-river is delineated by automating today's bathymetric data, in this instance 30Ã‚Â” General Bathymetric Chart of the Ocean (GEBCO), with the basis of Single Flow Direction, specifically The Basic Deterministic D8 algorithm. The result shows that paleo-river model is reasonably connected to dry-land river, particularly in estuary zones, with the farthest discrepancy of 9.3 km. This research also includes new evidences from geophysical investigation in the present Java Sea. It confirms elongated depression which could possibly identified as parts of paleo-river corresponding to the ancient East Sunda River. The findings are proposed for broader reconstruction purposes, such as biogeography, climate, and migrations.